Comprehensive analysis of ESCRT transcriptome-associated signatures and identification of the regulatory role of LMO7-AS1 in osteosarcoma - Shibing Zhao; Dasheng Tian; Fei Huang; Lei Wang; Jinhao Cheng; Zhitao He; Qitian Shen; Shuai Liang; Deliang Gong; Jun Liu; Chengfeng Yi; Chun Zhang; et al. (Cancer Cell International)
Abstract Osteosarcoma (OS) is a commonly observed malignant tumor in orthopedics that has a very poor prognosis. The endosomal sorting complex required for transport (ESCRT) is important for the development and progression of cancer and may be a significant target for cancer therapy. First, we built a prognostic signature using 7 ESCRT-related genes (ERGs) to predict OS patient prognosis. Analysis of internal and external datasets revealed that the ERG signature has good predictive ability and reproducibility. Immune analysis demonstrated a significant correlation between OS patient immune status and ERG signature score. Moreover, ERG signature score was found to be associated with the response of OS patients to immunotherapy and anticancer drugs. Additionally, we constructed a prognostic signature consisting of 10 ESCRT-related long noncoding RNAs (ERLs) that effectively predicted the prognosis of OS patients. Furthermore, two subgroups of OS patients with distinct prognoses (clusters 1 and 2) were identified. Finally, LMO7-AS1 was chosen for functional experimental validation. The knockdown of LMO7-AS1 suppressed the malignant progression of OS cells. Furthermore, transcriptome sequencing was performed on OS cells and revealed a correlation between LMO7-AS1 and the PI3K-Akt signaling pathway. In conclusion, our ESCRT transcriptome-associated signatures can act as prognostic biomarkers for OS, and LMO7-AS1 is a novel therapeutic target for the treatment of OS.